2021
DOI: 10.1038/s41598-021-87217-8
|View full text |Cite
|
Sign up to set email alerts
|

An acute phase protein α1-acid glycoprotein mitigates AKI and its progression to CKD through its anti-inflammatory action

Abstract: The molecular mechanism for acute kidney injury (AKI) and its progression to chronic kidney disease (CKD) continues to be unclear. In this study, we investigated the pathophysiological role of the acute phase protein α1-acid glycoprotein (AGP) in AKI and its progression to CKD using AGP KO mice. Plasma AGP levels in WT mice were increased by about 3.5-fold on day 1–2 after renal ischemia–reperfusion (IR), and these values then gradually decreased to the level before renal IR on day 7–14. On day 1 after renal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, AGP has an inhibitory action upon platelet aggregation [27]. Some studies demonstrated an anti-inflammatory effect of AGP [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AGP has an inhibitory action upon platelet aggregation [27]. Some studies demonstrated an anti-inflammatory effect of AGP [29].…”
Section: Discussionmentioning
confidence: 99%
“…CRP and AGP were cited as biomarkers in the prediction of all-cause mortality [27,28]. Besides the fact that AGP levels increase in systemic inflammation, this molecule has antiinflammatory and immunomodulatory effects [29][30][31], being a well-known inhibitor of neutrophiles and of the complement system [32,33]. AGP has another important function: it binds and transports endogen ligands related to inflammation and many drugs; thus, it is involved in the modulation of pharmacodynamics and pharmacokinetics of medicines [33].…”
Section: Introductionmentioning
confidence: 99%
“…Three-micrometer sections were stained with periodic acid-Schiff reagent (Cosmo Bio, Tokyo, Japan). Tubular injuries were defined as tubular necrosis, cast formation, loss of the brush border, and tubular vacuolization ( 31 ). At least four fields at ×200 magnification from each sample were scored as follows: 0, normal; 1, percentage of injury tubules ≤10%; 2, 11–25%; 3, 26–45%; 4, 46–75%; and 5: ≥75%, as previously described elsewhere ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tubular injuries were defined as tubular necrosis, cast formation, loss of the brush border, and tubular vacuolization ( 31 ). At least four fields at ×200 magnification from each sample were scored as follows: 0, normal; 1, percentage of injury tubules ≤10%; 2, 11–25%; 3, 26–45%; 4, 46–75%; and 5: ≥75%, as previously described elsewhere ( 31 ). For the analysis of kidney fibrosis, deparaffinized sections were incubated with picrosirius red solution (Cosmo Bio) for 1 h at room temperature and washed with acetic acid water.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, urinary excretion of orosomucoid increases in patients with type 2 diabetes and may be a biomarker for EC dysfunction due to low-grade inflammation ( 262 ). In triple (ORM1-3) knockout mice (unlike humans, mice have 3 ORM genes), enhanced inflammation and a greater susceptibility to renal fibrosis in the unilateral ureteral obstruction ( 263 ) and acute ischemia-reperfusion ( 264 ) models have been reported. At this time, quantitative glomerular permselectivity studies in ORM deficient mice are lacking.…”
Section: Circulating Proteins In the Endothelial Surface Layermentioning
confidence: 99%